Perfusion Flow Enhances Osteogenic Gene Expression and the Infiltration of Osteoblasts and Endothelial Cells into Three-Dimensional Calcium Phosphate Scaffolds - Barron, Matthew J.; Goldman, Jeremy; Tsai, Chung-Jui; Donahue, Seth W. (International Journal of Biomaterials, 2012)
Maintaining cellular viability in vivo and in vitro is a critical issue in three-dimensional bone tissue engineering. While the use of osteoblast/endothelial cell cocultures on three-dimensional constructs has shown promise for increasing in vivo vascularization, in vitro maintenance of cellular viability remains problematic. This study used perfusion flow to increase osteogenic and angiogenic gene expression, decrease hypoxic gene expression, and increase cell and matrix coverage in osteoblast/endothelial cell co-cultures. Mouse osteoblast-like cells (MC3T3-E1) were cultured alone and in co-culture with mouse microvascular endothelial cells (EOMA) on three-dimensional scaffolds for 1, 2, 7, and 14 days with or without perfusion flow. mRNA levels were determined for several osteogenic, angiogenic, and hypoxia-related genes, and histological analysis was performed. Perfusion flow downregulated hypoxia-related genes (HIF-1α, VEGF, and OPN) at early timepoints, upregulated osteogenic genes (ALP and OCN) at 7 days, and downregulated RUNX-2 and VEGF mRNA at 14 days in osteoblast monocultures. Perfusion flow increased cell number, coverage of the scaffold perimeter, and matrix area in the center of scaffolds at 14 days. Additionally, perfusion flow increased the length of endothelial cell aggregations within co-cultures. These suggest perfusion stimulated co-cultures provide a means of increasing osteogenic and angiogenic activity.